ISOLASI FRAGMEN cDNA DARI GEN PENYANDI AKTIN DARI Melastoma malabathricum - Hannum, Saleha; Akashi, Kinya; Suharsono, Utut Widyastuti; Hartana, Alex (Makara Journal of Science, 2010)
Isolation of cDNA Fragment of Gene Encoding for Actin from Melastoma malabthricum. M. malabathricum grows well in acidic soil with high Al solubility, thereby it can be used as a model plant for tolerance to aluminum and acid stresses. Actin is housekeeping gene used as an internal control for gene expression analysis. The objective of this research was to isolate and clone the cDNA fragments of MmACT encoding for actin of M. malabathricum. Total RNA was isolated and used as the template for cDNA synthesis by reverse transcription. Four cDNA fragments of MmACT, called MmACT1, MmACT2, MmACT3, and MmACT4, had been isolated and inserted into pGEM-T Easy plasmid. Nucleotide sequence analysis showed that the size of MmACT1 and MmACT2 is 617 bp, whereas MmACT3 and MmACT4 is 735 bp. The similarity among these four MmACT is about 78%-99% based on nucleotide sequence and about 98%-100% based on amino acid sequence. Phylogenetic analysis based on amino acid sequence showed that at 1% dissimilarity, the MmACT1, MmACT2, MmACT3 and the ACT5 Populus trichocarpha are clustered in one group, while the MmACT4 is grouped with ACT9 P. trichocarpa and ACT1 Gossypium hirsutum, and these two groups are separated from actin group of monocotyledonous plants. The sequence of MmACT fragments were registered in GenBank/EMBL/DDBJ database with accession numbers AB500686, AB500687, AB500688, and AB500689.